KONSEP BELAJAR MENURUT ISLAM - Parni Parni (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
The concept of learning in Islam really emphasizes the importance of knowledge. What's more, there are many verses in the Al-Quran which confirm this, even in the Hadith they carry out similar actions in explaining the importance of learning.